Analysis of Factors Causing Sports Injuries in Students' Interest and Talent in Football Sports Reviewed from Player Positions(Analysis Study on Students' Interest in Sports Talent) - Ramadhan, Lucky Adhitya; Fatoni, Muhad; Warthadi, Anugrah Nur (Fair Play, 2025)
This study aims to analyze and determine the percentage of sports injuries and the factors causing sports injuries viewed from the position of the players in students of sports talent interest (MBO) football Physical Education, Muhammadiyah University of Surakarta. This study uses a quantitative descriptive approach with data collection techniques using questionnaires. The research sample consisted of 26 MBO students from the 2021-2024 intake who had a history of sports injuries when playing football and were willing to be studied. Data analysis used the chi-square test to determine the relationship between sports injuries and player positions. The results of this study indicate that the most common injury experienced by MBO football students when playing football is ankle injury (65.38% from various positions). While the biggest factor that influences sports injuries in MBO football students is external factors, namely field conditions and contact with other athletes, each of which is 38.46%. The results of the Chi-Square test that has been carried out concluded that there is no significant relationship between sports injuries and player positions.